2017
DOI: 10.1002/ange.201701169
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐Promiskuität einer thermostabilen Transketolase durch gelenkte Evolution – effektive Komplementierung der 1‐Desoxy‐d‐ xylulose‐5‐phosphat‐Synthase‐Aktivität

Abstract: Enzyme,d ie asymmetrische C-C-Verknüpfungen katalysieren, sind typischerweise hochs pezifisch füri hre nukleophilen Donorsubstrate.M ittels strukturbasierter gerichteter Evolution konnten neue Enzymvarianten der thermostabilen Transketolase aus Geobacillus stearothermophilus erzeugt werden, die anstelle ihrer natürlichen Substrate,w ie polyhydroxylierte Ketosephosphate oder Hydroxypyruvat, auch Pyruvat und dessen hçhere aliphatische Homologe als Nukleophile fürd en Acyltransfer verwenden kçnnen. Die Einfachvar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Following the principle of the microreversibility of TK gst reaction, we expected that the combination of L118I with the single position H102L or with the double‐site mutation H102L/H474 (S or G) could lead to the desired products with high efficiency. Indeed, the active site analysis showed that the double variant H102L/H474 (S or G) [10a] greatly improved the substrate affinity toward pyruvate analogs including oxobutyrate. The presence of smaller and less polar side chains in place of the two histidine allowed enlargement of active site for bigger hydrophobic donor substrates and kept the catalytic mechanism intact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the principle of the microreversibility of TK gst reaction, we expected that the combination of L118I with the single position H102L or with the double‐site mutation H102L/H474 (S or G) could lead to the desired products with high efficiency. Indeed, the active site analysis showed that the double variant H102L/H474 (S or G) [10a] greatly improved the substrate affinity toward pyruvate analogs including oxobutyrate. The presence of smaller and less polar side chains in place of the two histidine allowed enlargement of active site for bigger hydrophobic donor substrates and kept the catalytic mechanism intact.…”
Section: Resultsmentioning
confidence: 99%
“…Expression was carried out in E. coli BL21(DE3)pLysS strain. This strain was transformed by heat shock with the following TK gst variants: artificial wild type TK gst , [9] H102L/H474S, [10a] H102L/L118I/H474S, [10b] H102L/L118I/H474G, [10b] and H102L/L118I [10b] . DAAO Rg was overexpressed [16] with the plasmid pT7.…”
Section: Methodsmentioning
confidence: 99%